Pyrophyllite tin bath bottom brick and preparation method thereof
By using natural raw material wool instead of pre-synthetic raw materials, the preparation of wool tin tank bottom bricks is solved, and the problems of high energy consumption and high cost of tin tank bottom bricks are achieved in the existing technology, and the production of tin tank bottom bricks with low energy consumption and low cost are achieved, and the product performance is excellent.
Patent Information
- Application Number
- CN202411986149.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2044-12-31
AI Technical Summary
The existing tin tank bottom bricks have high energy consumption during the manufacturing process, and the pre-synthetic raw materials used increase production costs and affect the promotion and use of products.
The natural raw material lene as aggregate and matrix is used instead of pre-synthetic raw materials. The preparation method of lene tin tank bottom bricks includes blank production, sintering and cutting processing to reduce manufacturing energy consumption and cost.
It greatly reduces the manufacturing energy consumption and cost of tin tank bottom bricks, meets the needs of use, and has low thermal conductivity, low hydrogen diffusion rate and good alkali corrosion resistance, extending the service life of the kiln.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of tin bath bottom bricks, in particular to a pyrophyllite tin bath bottom brick and a preparation method thereof. Background Art
[0002] Glass melting furnace is the core equipment in the production process of float glass, and tin bath is the core part of the overall manufacturing equipment. The quality of tin bath bottom brick is extremely important for the quality control of glass production process and the life of the furnace. The ideal tin bath bottom brick should have the following characteristics: smooth surface, no cracks, no impurities, precise size, uniform internal structure, low hydrogen diffusion rate, low permeability, low thermal expansion rate, low thermal conductivity, and no reaction with tin liquid and alkali metal oxides.
[0003] There are two types of tin bath bottom bricks that are more common on the market. One type is the silicon-aluminum clay tin bath bottom brick with an Al2O3 ratio of 40-55wt.%. For this type of tin bath bottom brick, most manufacturers need to use pre-synthesized aggregates. In addition, the clay tin bath bottom brick has high air permeability and poor corrosion resistance. It is easy to absorb Na2O from the glass liquid, react with Al2O3 and SiO2 in the brick material, and form nepheline compounds on the surface where the brick material contacts the tin liquid, accompanied by volume expansion. When the reaction products accumulate to a certain extent, they will peel off and float into the tin liquid, causing glass defects; the other type is the calcium aluminate tin bath bottom brick with an Al2O3 ratio of 67-76wt.%, CaO ratio of 21-28wt.%, and SiO2 ratio of 1.5-5wt.%. This type of tin bath bottom brick does not react with the tin liquid or Na2O, and has a long service life. However, this type of tin bath bottom brick is easy to undergo hydration reaction with water, and isostatic pressing is often used, which is expensive.
[0004] Chinese invention patent CN117720359A discloses low thermal conductivity tin bath bottom bricks and their preparation method, the raw materials used are: 45-70 parts of synthetic material, 10-16 parts of microporous mullite aggregate, 5-7 parts of pure calcium aluminate cement, and 11-25 parts of high temperature cement. The synthetic material and microporous mullite aggregate used in this method need to be pre-synthesized, wherein the synthetic material is extruded and then calcined, crushed, screened, etc. before it can be used; the production of microporous mullite aggregate is even more complicated, and it needs to be ground, dried, electrofused, crushed, and screened before it can be used, and the raw materials used consume a lot of energy during the preparation process.
[0005] Chinese invention patent CN102557688B discloses a method for preparing isostatically pressed aluminum-calcium-silica tin bath bottom bricks. Although the tin bath bottom bricks do not react with Na2O and have a long service life, the aggregates used in production need to be pre-synthesized, which consumes a lot of energy, and the isostatic pressing process itself has a high production cost, resulting in the high price of the tin bath bottom bricks, which affects their promotion and use in float glass kilns at home and abroad.
[0006] The glass manufacturing industry is a large energy consumer, so it is particularly urgent to develop a tin bath bottom brick that has low energy consumption in the manufacturing process and can meet the requirements of use. Summary of the invention
[0007] The technical problem to be solved by the present invention is: to overcome the shortcomings of the prior art, to provide pyrophyllite tin bath bottom bricks and a preparation method thereof, to select natural raw material pyrophyllite as aggregate and matrix to replace the existing pre-synthesized raw materials, to greatly reduce the use of artificial synthetic raw materials, to greatly reduce manufacturing energy consumption and costs, and the product quality also meets the use requirements.
[0008] The technical solution of the present invention is:
[0009] In one aspect, the present invention provides a pyrophyllite tin bath bottom brick, which is made of the following raw materials in parts by weight:
[0010] Pyrophyllite 40.5-60.5 parts
[0011] 25-45 pieces of coke gemstone
[0012] 3-7 parts of clay powder
[0013] Silica powder 1-5 parts
[0014] Quartz powder 0.5-4.5 parts
[0015] 2-6 parts of high alumina cement
[0016] Additives 0.1-0.35 parts;
[0017] Among them, in pyrophyllite, Al2O3>26wt.%, SiO2<70wt.%, Fe2O3<0.5wt.%, K2O+Na2O<0.5wt.%; in pyrophyllite, the content of pyrophyllite with a particle size of 1-3mm is 9-19wt.%, the content of pyrophyllite with a particle size of 0.1-1mm is 9-19wt.%, and the content of pyrophyllite with a particle size of <240 mesh is 17.5-27.5wt.%.
[0018] Preferably, in the coke gemstone, 44wt.%<Al2O3<55wt.%, 40wt.%<SiO2<52wt.%.
[0019] Preferably, in the coke gemstone, the content of coke gemstone with a particle size of 5-8 mm is 5-15wt.%, the content of coke gemstone with a particle size of 3-5 mm is 15-25wt.%, and the content of coke gemstone with a particle size of less than 240 mesh is 0-10wt.%.
[0020] Preferably, in the clay fine powder, Al2O3>30wt.%, 50wt.%<SiO2<65wt.%.
[0021] Preferably, in the silicon micropowder, SiO2>90wt.%.
[0022] Preferably, in the quartz powder, SiO2>90wt.%.
[0023] Preferably, in the high alumina cement, 45wt.%<Al2O3<65wt.%, 30wt.%<CaO<40wt.%.
[0024] Preferably, the additive is one or two of KAD-40, HDS-1 and 380S, which mainly play the role of dispersing, reducing water and accelerating hardness.
[0025] On the other hand, the present invention provides a method for preparing the above-mentioned pyrophyllite tin bath bottom brick, comprising the following steps:
[0026] S1 green body production: add water to each raw material and mix evenly, pour into the mold and vibrate to exhaust, place to solidify, and demold to obtain the green body;
[0027] S2 sintering: drying the green body obtained in step S1 in a drying kiln, and then loading it into a kiln for sintering;
[0028] S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
[0029] Preferably, in step S2, the drying temperature is 100-120°C, and the drying time is more than 48 hours; the sintering temperature is 1250-1400°C, and the sintering time is more than 20 hours.
[0030] Compared with the prior art, the present invention has the following beneficial effects:
[0031] 1. The present invention has made innovations and breakthroughs in the selection of raw materials when preparing tin bath bottom bricks. The natural raw material pyrophyllite is selected as aggregate and matrix to replace the existing pre-synthesized raw materials, greatly reducing the use of artificial synthetic raw materials, and no secondary calcination is required, which greatly reduces the manufacturing energy consumption and cost, and the product quality also meets the use requirements. The present invention introduces pyrophyllite as a raw material when preparing the tin bath bottom bricks. The obtained tin bath bottom brick has a low volume density, which is conducive to reducing the thermal conductivity of the tin bath bottom bricks, making it more energy-efficient during use. At the same time, the pyrophyllite tin bath bottom brick of the present invention has an extremely low hydrogen diffusion rate and good alkali corrosion resistance, which is conducive to improving the quality of glass production and extending the service life of the kiln.
[0032] 2. The amount of high-alumina cement added in the present invention is small, the fluidity is good during the molding process of the tin bath bottom brick, the semi-finished product has excellent strength after solidification, and the deformation and cracking formed when the product is dried are reduced. In addition, the pyrophyllite tin bath bottom brick of the present invention has a simple formula, requires fewer types of raw materials, and is conducive to production operation and large-scale production. DETAILED DESCRIPTION
[0033] In order to enable persons skilled in the art to better understand the technical solution of the present invention, the technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention.
[0034] The raw materials in the following examples and comparative examples are all commercially available raw materials, and the chemical composition test results of each raw material are shown in Table 1:
[0035] Table 1 Chemical composition test results of each raw material
[0036]
[0037] Example 1
[0038] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 3 parts of silicon powder, 2 parts of quartz powder, 4 parts of high alumina cement, and 0.3 parts of additive HDS-1.
[0039] The preparation method of the pyrophyllite tin bath bottom brick of the present embodiment comprises the following steps:
[0040] S1 green body preparation: add all raw materials into water accounting for 7% of the total mass of raw materials, stir for 5 minutes, pour into the mold and vibrate to exhaust for 3 minutes, place to solidify, naturally cure for 24 hours, and demold to obtain the green body;
[0041] S2 sintering: The green body is dried in a drying kiln at 110°C for 72 hours, and then sintered in a shuttle kiln at 1300°C for 24 hours;
[0042] S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
[0043] Example 2
[0044] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 25 parts of coke gemstone, 60.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 3 parts of silicon micropowder, 2 parts of quartz powder, 4 parts of high alumina cement, and 0.3 parts of additive KAD-40.
[0045] The preparation method of the pyrophyllite tin bath bottom brick of the present embodiment comprises the following steps:
[0046] S1 green body preparation: add all raw materials into water accounting for 7% of the total mass of raw materials, stir for 5 minutes, pour into the mold and vibrate to exhaust for 3 minutes, place to solidify, naturally cure for 24 hours, and demold to obtain the green body;
[0047] S2 sintering: The green body is dried in a drying kiln at 100°C for 72 hours, and then sintered in a shuttle kiln at 1250°C for 24 hours;
[0048] S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
[0049] Example 3
[0050] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 3 parts of silicon micropowder, 2 parts of quartz powder, 4 parts of high alumina cement, and 0.3 parts of additive 380S.
[0051] The preparation method of the pyrophyllite tin bath bottom brick of the present embodiment comprises the following steps:
[0052] S1 green body preparation: add all raw materials into water accounting for 7% of the total mass of raw materials, stir for 5 minutes, pour into the mold and vibrate to exhaust for 3 minutes, place to solidify, naturally cure for 24 hours, and demold to obtain the green body;
[0053] S2 sintering: The green body is dried in a drying kiln at 120°C for 48 hours, and then sintered in a shuttle kiln at 1400°C for 20 hours;
[0054] S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
[0055] Example 4
[0056] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 45 parts of coke gemstone, 40.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 3 parts of silicon micropowder, 2 parts of quartz powder, 4 parts of high alumina cement, 0.1 parts of additive HDS-1, and 0.2 parts of additive KAD-40.
[0057] The preparation method of the pyrophyllite tin bath bottom brick of the present embodiment comprises the following steps:
[0058] S1 green body preparation: add all raw materials into water accounting for 7% of the total mass of raw materials, stir for 5 minutes, pour into the mold and vibrate to exhaust for 3 minutes, place to solidify, naturally cure for 24 hours, and demold to obtain the green body;
[0059] S2 sintering: The green body is dried in a drying kiln at 110°C for 72 hours, and then sintered in a shuttle kiln at 1300°C for 24 hours;
[0060] S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
[0061] Example 5
[0062] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 3 parts of Guangxi soil, 3 parts of silicon micropowder, 4.5 parts of quartz powder, 4 parts of high alumina cement, 0.05 parts of additive HDS-1, and 0.1 parts of additive 380S.
[0063] The preparation method of the pyrophyllite tin bath bottom brick of this embodiment is the same as that of Example 1.
[0064] Example 6
[0065] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 7 parts of Guangxi soil, 3 parts of silicon micropowder, 0.5 parts of quartz powder, 4 parts of high alumina cement, 0.05 parts of additive KAD-40, and 0.3 parts of additive 380S.
[0066] The preparation method of the pyrophyllite tin bath bottom brick of this embodiment is the same as that of Example 1.
[0067] Example 7
[0068] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 5 parts of silicon micropowder, 2 parts of quartz powder, 2 parts of high alumina cement, 0.3 parts of additive KAD-40, and 0.05 parts of additive 380S.
[0069] The preparation method of the pyrophyllite tin bath bottom brick of this embodiment is the same as that of Example 1.
[0070] Example 8
[0071] The pyrophyllite tin bath bottom brick of this embodiment is made of the following raw materials in parts by weight: 35 parts of coke gemstone, 50.5 parts of pyrophyllite, 5.5 parts of Guangxi soil, 1 part of silicon micropowder, 2 parts of quartz powder, 6 parts of high alumina cement, 0.05 parts of additive HDS-1, and 0.05 parts of additive KAD-40.
[0072] The preparation method of the pyrophyllite tin bath bottom brick of this embodiment is the same as that of Example 1.
[0073] The content of each raw material, the particle size composition of coke gemstone, and the particle size composition of pyrophyllite in Examples 1-8 are shown in Table 2-4 respectively:
[0074] Table 2 Content of each raw material in Examples 1-8
[0075]
[0076] Table 3 Particle size composition of coke gemstones in Examples 1-8
[0077]
[0078] Table 4 Particle size composition of pyrophyllite in Examples 1-8
[0079]
[0080] Comparative Example 1
[0081] The difference between Comparative Example 1 and Example 1 is that 40 synthetic material is used to replace the pyrophyllite in Example 1.
[0082] Comparative Example 2
[0083] The difference between Comparative Example 2 and Example 2 is that 40 synthetic material is used to replace the pyrophyllite in Example 2.
[0084] Comparative Example 3
[0085] The difference between Comparative Example 3 and Example 3 is that 40 synthetic material is used to replace the pyrophyllite in Example 3.
[0086] Comparative Example 4
[0087] The difference between Comparative Example 4 and Example 4 is that 40 synthetic material is used to replace the pyrophyllite in Example 4.
[0088] Comparative Example 5
[0089] The difference between Comparative Example 5 and Example 1 is that it is made of the following raw materials in parts by weight: 65.5 parts of talc, 20 parts of charcoal, 5.5 parts of Guangxi soil, 3 parts of silicon micropowder, 2 parts of quartz powder, 4 parts of high alumina cement, and 0.3 parts of additive HDS-1.
[0090] Comparative Example 6
[0091] The difference between Comparative Example 6 and Example 1 is that the particle size composition of pyrophyllite is as follows: the content of pyrophyllite with a particle size of 1-3 mm is 24 wt.%, the content of pyrophyllite with a particle size of 0.1-1 mm is 14 wt.%, and the content of pyrophyllite with a particle size of less than 240 mesh is 22.5 wt.%.
[0092] Comparative Example 7
[0093] The difference between Comparative Example 7 and Example 1 is that the particle size composition of pyrophyllite is as follows: the content of pyrophyllite with a particle size of 1-3 mm is 14 wt.%, the content of pyrophyllite with a particle size of 0.1-1 mm is 24 wt.%, and the content of pyrophyllite with a particle size of less than 240 mesh is 22.5 wt.%.
[0094] Comparative Example 8
[0095] The difference between Comparative Example 8 and Example 1 is that the particle size composition of pyrophyllite is as follows: the content of pyrophyllite with a particle size of 1-3 mm is 14 wt.%, the content of pyrophyllite with a particle size of 0.1-1 mm is 14 wt.%, and the content of pyrophyllite with a particle size of less than 240 mesh is 30.5 wt.%.
[0096] Comparative Example 9
[0097] The difference between Comparative Example 9 and Example 1 is that the chemical composition of talc is: 69.88wt.% SiO2, 27.42wt.% Al2O3, 1.17wt.% Fe2O3, 0.8wt.% TiO2, 0.02wt.% CaO, 0.05wt.% MgO, 0.28wt.% Na2O, and 0.38wt.% K2O.
[0098] The construction performance of the raw materials in Examples 1-8 and Comparative Examples 1-9 and the performance of the prepared tin bath bottom bricks were tested, and the test results are shown in Tables 5-7. The test method for mold filling capacity is as follows: the mixed mud is poured into a rectangular mold, and the mud self-flowing fills the four corners of the model as excellent, the mud self-flowing fills the three corners of the model as average, the mud self-flowing fills the two corners of the model as poor, and the mud self-flowing fills less than one corner of the model as unconstructable. The initial setting time is tested in accordance with GB / T 50080-2016 Standard for Test Methods for Properties of Ordinary Concrete Mixtures; the apparent porosity and bulk density are tested in accordance with GB / T 2997-2015 Test Methods for Bulk Density, Apparent Porosity and True Porosity of Dense Shaped Refractory Products; the compressive strength is tested in accordance with GB / T5072-2023 Test Method for Compressive Strength of Refractory Materials at Room Temperature; the load softening temperature is tested in accordance with GB / T5989-2008 Test Method for Load Softening Temperature of Refractory Materials - Differential Heating Method; the hydrogen diffusion rate is tested in accordance with JC / T 926-2003 Tin Bath Bottom Bricks for Float Glass Kiln.
[0099] Table 5 Construction performance test results of raw materials in Examples 1-8 and Comparative Examples 1-9
[0100]
[0101] Table 6 Physical property test results of tin bath bottom bricks prepared in Examples 1-8
[0102]
[0103] Table 7 Physical property test results of tin bath bottom bricks prepared in Comparative Examples 1-9
[0104]
[0105] It can be seen from Example 1 and Example 2-4 in Table 5 that when the amount of pyrophyllite added is adjusted within an appropriate range, the tin bath bottom brick can be constructed normally; it can be seen from Example 1 and Example 5-8 that when the amount of clay fine powder (i.e., Guangxi soil) and silicon micropowder, the amount of high-aluminum cement and additives are adjusted, the construction performance of the tin bath bottom brick will be affected. According to the temperature, humidity and brick size of the construction site, the amount of clay fine powder, silicon micropowder, high-aluminum cement and additives can achieve good construction effects within the scope defined by the present invention. It can be seen from further comparison of Example 1-4 and Comparative Example 1-4 in Table 5 that when pyrophyllite is replaced with the commonly used 40 synthetic material, normal construction can be achieved. It can be seen from further comparison of Example 1 and Comparative Example 5-8 in Table 5 that when pyrophyllite is added too much or the content of each particle size range of pyrophyllite exceeds the limited range of the present invention, the construction performance of the tin bath bottom brick will be adversely affected, resulting in poor mold filling ability. Further comparison of Example 1 and Comparative Example 9 in Table 5 shows that normal construction is possible even after the chemical composition of pyrophyllite changes.
[0106] As shown in Table 6, the tin bath bottom bricks prepared in Examples 1-4 have an apparent porosity of 24.8-25.7% and a bulk density of 1.98-2.05 g / cm 3 The compressive strength is between 33-37 MPa, the refractoriness under load temperature T2 is between 1342-1358°C, and the hydrogen diffusion rate is between 5-17 mmH2O. By comparing Example 1 with Examples 5-8 in Table 6, it can be seen that when the amount of clay fine powder and silicon powder, the amount of high alumina cement and additives are appropriately adjusted within the range defined by the present invention, the performance of the prepared tin bath bottom bricks is not much different.
[0107] By comparing Examples 1-4 and Comparative Examples 1-4 in Table 7, it can be seen that by replacing the pyrophyllite in Examples 1-4 with the commonly used 40 synthetic material, the apparent porosity of the tin bath bottom bricks obtained is between 15.4-17.6%, and the bulk density is between 2.15-2.21 g / cm 3The compressive strength is between 45-57.1MPa, the load softening temperature T2 is between 1337-1346℃, and the hydrogen diffusion rate is between 75-116mmH2O. Compared with Comparative Examples 1-4, the apparent porosity of the tin bath bottom bricks prepared by pyrophyllite in Examples 1-4 is improved, the bulk density is reduced, and the hydrogen diffusion rate is significantly reduced. It is speculated that during the sintering stage of the tin bath bottom bricks, after the combined water is discharged, a large number of closed pores are formed in situ by pyrophyllite, which is beneficial to improving the hydrogen diffusion resistance of the tin bath bottom bricks. In addition, the reduced bulk density and increased apparent porosity of the tin bath bottom bricks are also beneficial to reducing the thermal conductivity of the tin bath bottom bricks, making the tin bath bottom bricks more energy-efficient during use. Further comparison of Example 1 and Comparative Example 9 in Table 7 shows that when the grade of the pyrophyllite used decreases, the load softening temperature T2 of the prepared tin bath bottom bricks is significantly reduced, which makes its structural stability in a high temperature and high pressure environment worse.
Claims
1. Pyrophyllite tin bath bottom brick, characterized in that: Made from the following raw materials in parts by weight: Pyrophyllite 40.5-60.5 parts 25-45 pieces of coke gemstone 3-7 parts of clay powder Silica powder 1-5 parts Quartz powder 0.5-4.5 parts 2-6 parts of high alumina cement Additives 0.1-0.35 parts; Among them, in pyrophyllite, Al2O3>26wt.%, SiO2<70wt.%, Fe2O3<0.5wt.%, K2O+Na2O<0.5wt.%; In the pyrophyllite, the content of pyrophyllite with a particle size of 1-3mm is 9-19wt.%, the content of pyrophyllite with a particle size of 0.1mm≤<1mm is 9-19wt.%, and the content of pyrophyllite with a particle size of <240 mesh is 17.5-27.5wt.%.
2. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: In the coke gemstone, 44wt.%<Al2O3<55wt.%, 40wt.%<SiO2<52wt.%.
3. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: Among the coke gemstones, the content of coke gemstones with a particle size of 5-8 mm is 5-15wt.%, the content of coke gemstones with a particle size of 3mm≤<5mm is 15-25wt.%, and the content of coke gemstones with a particle size of <240 mesh is 0-10wt.%.
4. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: In the clay fine powder, Al2O3>30wt.%, 50wt.%<SiO2<65wt.%.
5. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: In the silicon micropowder, SiO2>90wt.%.
6. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: In the quartz powder, SiO2>90wt.%.
7. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: In the high alumina cement, 45wt.%<Al2O3<65wt.%, 30wt.%<CaO<40wt.%.
8. The pyrophyllite tin bath bottom brick according to claim 1, characterized in that: The additive is one or two of KAD-40, HDS-1 and 380S.
9. The method for preparing the pyrophyllite tin bath bottom brick according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1 green body production: add water to each raw material and mix evenly, pour into the mold and vibrate to exhaust, place to solidify, and demold to obtain the green body; S2 sintering: drying the green body obtained in step S1 in a drying kiln, and then loading it into a kiln for sintering; S3 Cutting and grinding: After the sintered green body is cut and ground into the required shape and size, the pyrophyllite tin bath bottom brick is obtained.
10. The method for preparing the pyrophyllite tin bath bottom brick according to claim 9, characterized in that: In step S2, the drying temperature is 100-120°C, and the drying time is more than 48 hours; the sintering temperature is 1250-1400°C, and the sintering time is more than 20 hours.
Citation Information
Patent Citations
Preparation method for isostatic pressure calcium-aluminum-silicon tin bath bottom brick
CN102557688B
Low-thermal-conductivity tin bath bottom brick and preparation method thereof
CN117720359A
Impermeable brick for aluminum electrolysis cell
CN112408964A
Bottom brick in tin pot
CN1480416A